2017
DOI: 10.21767/2572-5459.100021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Selenium Nanoparticles on Anti-Oxidative Level, Egg Production and Quality and Blood Parameter of Laying Hens Exposed to Deoxynivalenol

Abstract: The aim of this study was to investigate the efficacy of selenium nanoparticles (SeNPs) that had been biologically synthesized by Bacillus licheniformis to counteract deoxynivalenol (DON) toxicity in laying hens. Ninety-six healthy, 20-week-old laying hens were randomly assigned to four treatment groups, each of which included 3 replicates of 8 layers, and fed four different diets: an uncontaminated basal diet (control group), a 10 mg/kg DON-contaminated basal diet (DON group), a 10 mg/kg DON-contaminated basa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Some researchers indicated Se yeast might be a superior organic source of selenium compared to other selenite sources because of the better utilization and absorption by the animal [13][14][15][16]. Qu et al [17] reported that adding selenium nanoparticles in feed of laying hens had no effect on egg weight, Haugh units, yolk color, eggshell strength, and eggshell thickness. However, Se deposition in eggs from laying hens fed with different selenium sources and levels has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers indicated Se yeast might be a superior organic source of selenium compared to other selenite sources because of the better utilization and absorption by the animal [13][14][15][16]. Qu et al [17] reported that adding selenium nanoparticles in feed of laying hens had no effect on egg weight, Haugh units, yolk color, eggshell strength, and eggshell thickness. However, Se deposition in eggs from laying hens fed with different selenium sources and levels has not been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Supplementation of various sources of selenium to chicken, by Mohapatra et al, (2014) revealed higher GPx activity than nonsupplemented group and nano selenium improved GPx and SOD activity than sodium selenite supplemented groups. Similarly, Safdari-Rostamabad et al, (2017), Qu et al, (2017) and Li et al, (2018) observed linearly increased the activity of glutathione peroxidase by dietary supplementation of nano selenium. Contrary to the result obtained for nano selenium supplemented group Li et al, (2018) noticed no significant change in activity of SOD and catalase enzyme between treatments and control.…”
Section: Antioxidant Status Of Birdsmentioning
confidence: 84%
“…These results came inconsistent with Jia et al (2005) who reported that selenium is an essential trace element that is commonly used as an antioxidant for animals, but there is a very narrow margin between the safe and toxic nutrient levels. Also, Qu et al (2017) reported that, a new source of selenium is selenium nanoparticles (SeNPs) which exhibit the following properties: antioxidant, antibacterial activities, lower toxicity, better absorption and bioactivity. In addition, SeNPs decreased the oxidative stress in the hens, and improved the avian immune system status by alleviating the immunocompetent cells ability for an antigen challenge.…”
Section: Discussionmentioning
confidence: 99%